Intercalation and reactions of CO under single layer graphene/Ni(111): the role of vacancies. Issue 46 (21st November 2022) - Davì, Rocco; Carraro, Giovanni; Stojkovska, Marija; Smerieri, Marco; Savio, Letizia; Gallet, Jean-Jacques; Bournel, Fabrice; Rocca, Mario; Vattuone, Luca
Abstract : We use synchrotron radiation-induced core level photoemission spectroscopy to investigate the influence of vacancies, produced by ion bombardment, on monolayer graphene/Ni(111) exposed to CO at pressures ranging from ultra-high vacuum up to near ambient (5.6 mbar) conditions. Abstract : We use synchrotron radiation-induced core level photoemission spectroscopy to investigate the influence of vacancies, produced by ion bombardment, on monolayer graphene/Ni(111) exposed to CO at pressures ranging from ultra-high vacuum (10 −10 mbar) up to near ambient (5.6 mbar) conditions. CO intercalates at a rate which is comparable to the one observed in absence of defects and reacts via the Boudouard reaction producing additional carbon atoms and CO2 . While the former attach to the graphene layer and extend it over areas previously covered by carbide, the CO2 molecules bind to the graphene vacancies forming epoxy-like bonds across them, thus mending the defects. The so-formed complexes give rise to a peak at 533.4 eV which persists upon evacuating the vacuum chamber at room temperature and which we assign to a covalently bonded species containing C and O.